Prevention of diabetic foot ulcers using a smartphone and mobile thermography: a case study. (2nd February 2021) - Oe, Makoto; Tsuruoka, Kahori; Ohashi, Yumiko; Takehara, Kimie; Noguchi, Hiroshi; Mori, Taketoshi; Yamauchi, Toshimasa; Sanada, Hiromi
Abstract : Objective: Early identification of pre-ulcerative pathology is important to preventing diabetic foot ulcers (DFU), but signs of inflammation are difficult to detect on the feet of patients with diabetic neuropathy due to decreased sensation. However, infrared thermography can objectively identify inflammation. Therefore, a device that allows patients to visualise thermograms of their feet might be an effective way to prevent DFU. We aimed to determine the effects of a novel self-monitoring device to prevent DFU using a thermograph attached to a smartphone. Method: A self-monitoring device comprising a mobile thermograph attached to a smartphone on a selfie stick was created, and its effects in two patients with diabetic neuropathy and foot calluses assessed. Results: For one patient, he understood that walking too much increased the temperature in the skin of his feet (a sign of inflammation). The other patient could not detect high-risk findings, because the temperature of his skin did not increase during the study period. Conclusion: This device might provide self-care incentives to prevent DFU, although some issues, such as the automatic detection of high-risk thermographic changes, need to be improved.